Impact of textual warnings on emotional brain responses to ultra-processed food products - Fernandes, Thayane Ferreira da Costa; Ferreira, Naiane Beatriz; Campagnoli, Rafaela Ramos; Gomes, Fabio da Silva; Braga, Filipe; David, Isabel Antunes; Lobo, Isabela (Frontiers in Nutrition, 2022)
Background and Objectives: Ultra-processed food products (UPF) have been associated with numerous noncommunicable diseases. Despite this, the addictive nature of UPF, and the aggressive marketing strategies used to promote them, has created a strong emotional connection between UPF and consumers, and supports their increasing UPF global consumption. In view of the emotional link that consumers often have with UPF, modulating emotional reactions to UPF (by using strategies such as textual warnings) is important in changing consumers’ behavior. Since emotions are better understood by assessing individuals’ implicit reactions, we conducted an electroencephalographic study applying the event-related potential technique to investigate whether textual warnings were able to modulate the brain responses to UPF stimuli. Methods: Twenty-six participants (19 women) viewed pictures of UPF preceded by a warning sentence about the health risks of consuming UPF or a control sentence while the electroencephalogram was recorded. In addition, the participants rated the picture in respect of pleasantness, arousal, and intention to consume. As emotions are associated with motivational circuits in the brain, we focused on a well-known event-related potential brain marker of the motivational relevance associated with emotional stimuli, namely late positive potential (LPP). Results: The late positive potential amplitude was larger for pictures depicting UPF under the warning condition compared to the control condition, a result that was accompanied by lower pleasantness ratings during the warning condition (compared to the control). Conclusion: Textual warnings about the negative health consequences of consuming UPF changed the emotional responses toward UPF, possibly increasing the motivation to avoid UPF. These results shed new light on the impact of textual warnings on UPF-evoked emotions.